INNOVATIVE EXPERIENTIAL LEARNING–BASED LEADERSHIP TRAINING FOR TRANSFORMING STUDENT COMPETENCIES IN ORGANIZATIONAL CONTEXTS - Kintoko Kintoko; Ghea Nanda Triyulia; Deny Hadi Siswanto (CV. Denasya Smart Publisher, 2025)
This community engagement program aims to strengthen student leadership capacity through experiential learning–based training. The implementation method began with a needs assessment conducted through observation and discussions with the board members of the Mathematics Education Student Association at PGRI Yogyakarta University to identify participants’ initial understanding of leadership and organizational management. Based on the assessment results, a training plan was developed that included material design, instructional methods, selection of trainers, and preparation of evaluation instruments. The training was carried out using interactive lectures, simulations, case studies, and group discussions, followed by leadership practice and reflective activities. Monitoring and evaluation were conducted through questionnaires, interviews, observations, and analysis of pretest and posttest results. The findings demonstrated a significant improvement across all assessment components, particularly in strategic thinking, communication, decision-making skills, and the application of leadership roles within organizational contexts. Follow-up actions included continued organizational mentoring and the development of an advanced leadership improvement program. Thus, the training program proved effective in enhancing student leadership competence both conceptually and practically, and it holds strong potential for sustainable implementation within campus organizations.